Skill Analysis for Teachers: Considerations for Physical Education Teacher Education - DERVENT, FATİH (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
In this article, essential knowledge for teacher educators in the teaching of skill analysis is discussed. The research literature shows that preservice and practicing teachers are not well trained in skill analysis and content knowledge as they need to conduct and act on their diagnoses. First, the reasons why skill analysis deserves much more attention in teacher education are described. Next, skill analysis is defined and essential knowledge for teacher educators and teachers discussed. Finally, examples are provided for improving the practice of teaching skill analysis to preservice teachers.